The accuracy of a novel self‐tapping bone fiducial marker for frameless robot‐assisted stereo‐electro‐encephalography implantation and registration techniques. Issue 2 (17th December 2022) - Liu, Qiangqiang; Mao, Ziyu; Wang, Junjie; Wang, Changquan; Chen, Wenze; Chen, Wenzhen; Ye, Xiaolai; Zhang, Chencheng; Lu, Yong; Xu, Jiwen
Abstract: Background: We aimed to evaluate the accuracy and safety of a novel self‐tapping bone fiducial as a registration technique for stereoelectroencephalography (SEEG) implantation. Methods: Each patient was installed with five bone fiducial markers. All procedures were performed using the same Sinovation robot system. The accuracy was determined by calculating the target point error (TPE) and the entry point error (EPE) of electrodes. Results: Fourteen patients underwent SEEG implantation surgery; and the average installation time of the markers per patient was 86.1 s. In the operating theatre, the average registration time was 206.6 s, and the average registration error was 0.18 mm. The average TPE of 174 electrodes was 1.98 mm and the average EPE was 0.88 mm. Conclusion: Our study provided a bone fiducial marker installation and registration technique that was convenient and fast, highly accurate in registration, and highly tolerated by patients.